Flow Distribution Analysis in a Multi Inlet Gas Manifold Using Computational Fluid Dynamics - Jerico Justin; Abrar Riza; Steven Darmawan (Jurnal ASIIMETRIK Jurnal Ilmiah Rekayasa & Inovasi, 2026)
Manifolds are crucial components in various industries, particularly in oil and gas, agriculture, and energy distribution, where they function to combine fluid flow from multiple pathways into a single header pipe. Achieving uniform flow distribution is essential for maintaining system efficiency and reliability. However, non-uniform flow distribution frequently occurs due to differences in flow resistance, system geometry, and inter-stream interactions at each junction. To address the limitations of simplified analytical approaches such as the Bernoulli equation, which does not simultaneously accommodate viscosity, turbulence, and compressibility effects, a numerical approach based on Computational Fluid Dynamics was employed. This study aims to analyze the flow distribution characteristics, including velocity, pressure, and mass flow rate, in a seven inlet collector manifold, while comparing simulation results with the Bernoulli equation prediction and demonstrating consistency with the governing Navier–Stokes framework. Simulations were conducted in three dimensions using ANSYS Fluent with the SST k-ω turbulence model and the Peng–Robinson real gas model for methane at 136 bar and 70°C. Results revealed progressive flow maldistribution, with velocity increasing from 50 m/s at the inlets to 73.94 m/s at the outlet, accompanied by a total pressure drop of approximately 542 kPa. Density–velocity and density–total pressure correlations exhibited non-linear interdependencies consistent with the Navier–Stokes equations, confirming the significant roles of viscosity, turbulence, and compressibility effects within the system .